Wi-Fi 8: The Next Generation of Wireless Connectivity - Cox, Landon; Tang, Fengxiao; Zhao, Ming; Kato, Nei (GetMobile (New York, N.Y.))
Wi-Fi 8, defined by IEEE 802.11bn and expected to be certified in 2028, introduces Ultra High Reliability (UHR) to support mobile computing and the Internet of Things (IoT). Unlike previous standards, Wi-Fi 8 ensures sustained throughput and low-latency connectivity in congested, highinterference environments through innovations such as multi-access point coordination, distributed resource units, latency reduction, and dynamic power management. This study analyzes the technological advancements of Wi-Fi 8 and its applications in augmented reality, industrial IoT, and smart cities, providing insights such as scalable interference mitigation and global spectrum coordination for the 32 billion IoT devices expected to reach by 2030. This paper provides practical guidance for engineers and researchers to meet the challenges in high-interference environments.